Pengaruh Harga, Ulasan Produk, Kemudahan Dan Keamanan Terhadap Keputusan Pembelian Secara Online Di Shopee Pada Kecamatan Periuk Kota Tangerang - Fajri, Iqbal Hasan; Asiyah, Siti; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the influence of price, product reviews, convenience and security on online purchasing decisions at Shopee (Case Study in Periuk District, Tangerang City). The type of research used is quantitative research. Based on the results of research conducted, researchers used a questionnaire given to consumers in the Kampung Periuk Jaya area, RT/RW 02/02, Periuk Jaya Village, Periuk District, Tangerang City. Researchers got 85 respondents based on age. Sampling from this research used Purposive Sampling Technique. The analysis techniques used are respondent response regression, multiple linear regression, and coefficient of determination (R2). This research uses validity tests, reliability tests, and classical assumption tests followed by hypothesis testing. Based on the results of multiple linear regression analysis, the research results show that Price, Product Reviews, Convenience and Security have a partially significant effect on online purchasing decisions at Shopee. This is proven by the t test results showing that all variables have a significance value of <0.05. So it can be concluded that the Price variable (X1) has a significant negative effect on Purchasing Decisions, Product Reviews (X2) has a significant positive effect on Purchasing Decisions, Convenience (X3) has a significant positive effect on Purchasing Decisions, Security (X4) has a significant positive effect on Purchasing Decisions. Keywords: Price, Product Reviews, Convenience, Security, Online Purchases on Shopee